Project managers at work - Harpham, Bruce (Apress, 2018)
Read 25 in-depth, candid interviews with notable project managers. Discover how project managers work, what they do, how they adapt and make decisions, how they inspire and motivate others, what career lessons and advice they can share, and how they landed their current jobs either as project managers or in more senior positions thanks to their success as project managers. Most of the project managers featured in this book--together with a selection of program managers, executives, entrepreneurs, and CEOs with project management backgrounds and responsibilities--work in the technology sector, but many work in other industries, including banking and financial services, consulting, aerospace, energy, and transportation. Bruce Harpham, PMP--a project management career advisor and journalist--has chosen interviewees who range across the spectrum of company size and maturity and of individual career stages--from CEOs who were formerly project managers (such as Mavenlink's Ray Grainger); to founders of project management consulting firms (such as Tramore's Tom Atkins); to project managers at the world's leading tech giants (such as IBM's Bob Tarne, Google's Michael Lubrano, Apple's Seth J. Gillespie, and Cisco's Hassan Osman), in the space industry (such as NASA's David Woerner, Canadian Space Agency's Isabelle Tremblay and EUMETSAT's Hilary Wilson), in financial services (such as TD Bank's Ilana Sprongl and Ontario Municipal Employees Retirement System's Annette Lyjak), and at transportation and logistics companies (such as Amtrak's Sarina Arcari). What You'll Learn Practicing project managers and engineers and graduates who aspire to become project managers will learn from the mouths of seasoned exponents at the top of their profession: Break into project management, cultivate leadership skills, and influence higher-ups Win assignments to manage career-advancing projects and ace deliveries Avoid pitfalls and recover from operational failures and managerial mistakes Manage the distractions and pressures of project work successfully while maintaining high morale Discover the books, courses, and development strategies they used to make it to the top.
Includes index.
Keywords: Project managers -- Knowledge and learning.; Project managers -- Biography.; Project management.; elektronické knihy; electronic books